Severe Hyperthermia Induces Apoptosis Mediated by Caspases Activation and Suppression of Hsp90-alpha Expression in Osteosarcoma Cells - Mohammed Ali Nashiry; Gabriele Ruth Anisah Froemming; Yeap Swee Keong; Aletza Binti Mohd Ismail; Aisha Mohd Din; Alyaa Mahmood Al-Khateeb (The Indonesian Biomedical Journal, 2019)
BACKGROUND: Hyperthermia is used as an adjuvant treatment to sensitize cancer cells to subsequent radiotheraphy or chemotherapy. The aim of this study was to study the effect of severe hyperthermia on osteosarcoma cells and its underlying causes.METHODS: Short-term (1 h) severe hyperthermia (45°C) was applied to osteoblast-like osteosarcoma cells (MG-63) and the heat shock response and cell death mechanisms were investigated after recovery at 37°C for 72 h.RESULTS: Cell viability was significantly reduced (p<0.05) and apoptosis was significantly induced by severe hyperthermia in MG-63 cells (p<0.001). Caspase 3/7, 4 and 12 activities were significantly increased after 72 h of recovery at 37°C, indicating that severe hyperthermia induced endoplasmic reticulum (ER) stress and apoptosis (p<0.05). Heat shock protein 90 alpha (Hsp90α) was significantly down regulated at the protein level after recovery, in association with apoptosis induction (p<0.01). Additionally, caspase 8 and 9 were activated, possibly as a result of ER stress or other stimuli while, B-cell leukemia 2 family protein (BCL-2) mRNA was down regulated (p<0.01).CONCLUSION: Severe hyperthermia could cause prolonged cell cytotoxicity by inducing apoptosis in association with inhibition of Hsp90α. This indicates the therapeutic potential of severe hyperthermia for the treatment of osteosarcoma.KEYWORDS: hyperthermia, apoptosis, endoplasmic reticulum, stress, heat shock proteins, osteosarcoma